Cover Image, Volume 10, Issue 10. (12th October 2016) - Kitamura, Morimasa; Hirano, Shigeru; Kanemaru, Shin‐ichi; Kitani, Yoshiharu; Ohno, Satoshi; Kojima, Tsuyoshi; Nakamura, Tatsuo; Ito, Juichi; Rosen, Clark A.; Gilbert, Thomas W.
Abstract : The cover image, by Morimasa Kitamura et al., is based on the Research Article Glottic regeneration with a tissue‐engineering technique, using acellular extracellular matrix scaffold in a canine model†, DOI:10.1002/term.1855 .